Convergent evolution of disordered lipidic structural colour in the fruits of Lantana strigocamara (syn. L. camara hybrid cultivar). Issue 3 (10th June 2022) - Sinnott‐Armstrong, Miranda A.; Ogawa, Yu; van de Kerkhof, Gea Theodora; Vignolini, Silvia; Smith, Stacey D.
Summary: The majority of plant colours are produced by anthocyanin and carotenoid pigments, but colouration obtained by nanostructured materials (i.e. structural colours) is increasingly reported in plants. Here, we identify a multilayer photonic structure in the fruits of Lantana strigocamara and compare it with a similar structure in Viburnum tinus fruits. We used a combination of transmission electron microscopy (EM), serial EM tomography, scanning force microscopy and optical simulations to characterise the photonic structure in L. strigocamara . We also examine the development of the structure during maturation. We found that the structural colour derives from a disordered, multilayered reflector consisting of lipid droplets of c. 105 nm that form a plate‐like structure in 3D. This structure begins to form early in development and reflects blue wavelengths of light with increasing intensity over time as the structure develops. The materials used are likely to be lipid polymers. Lantana strigocamara is the second origin of a lipid‐based photonic structure, convergently evolved with the structure in Viburnum tinus . Chemical differences between the lipids in L. strigocamara and those of V. tinus suggest a distinct evolutionary trajectory with implications for the signalling function of structural colours in fruits.